Detectability of satellites around directly imaged exoplanets and brown dwarfs. Issue 1 (6th August 2022) - Lazzoni, Cecilia; Desidera, Silvano; Gratton, Raffaele; Zurlo, Alice; Mesa, Dino; Ray, Shrishmoy
ABSTRACT: Satellites around substellar companions are a heterogeneous class of objects with a variety of different formation histories. Focusing on potentially detectable satellites around exoplanets and brown dwarfs (BDs), we might expect to find objects belonging to two main populations: planet-like satellites similar to Titan or the Galileian Satellites – likely formed within the scope of core accretion; and binary-like objects, formed within different scenarios, such as disc instability. The properties of these potential satellites would be very different from each other. Additionally, we expect that their characterization would provide insightful information about the history of the system. This is particularly important for planets/BDs discovered via direct imaging (DI) with ambiguous origins. In this paper, we review different techniques, applied to DI planets/BDs, that can be used to discover such satellites. This was achieved by simulating a population of satellites around the exoplanet β  Pic b, which served as a test case. For each simulated satellite, the amplitude of DI, radial velocity, transit and astrometric signals, with respect to the planet, were retrieved and compared with the detection limits of current and future instruments. Furthermore, we compiled a list of 38 substellar companions discovered via DI to give a preliminary estimate on the probability of finding satellites extracted from the two populations mentioned above, with different techniques. This simplified approach shows that detection of planet-like satellites, though not strictly impossible, is very improbable. On the other hand, the detection of binary-like satellites is within the capabilities of current instrumentation.